Profiles of Psychological Flexibility: A Latent Class Analysis of the Acceptance and Commitment Therapy Model. Issue 3 (May 2020) - Tyndall, Ian; Waldeck, Daniel; Pancani, Luca; Whelan, Robert; Roche, Bryan; Pereira, Antonina
There exists uncertainty for clinicians over how the separate subcomponent processes of psychological flexibility, a core construct of the Acceptance and Commitment Therapy model, interact and influence distress experienced. The present study ( N = 567) employed latent class analysis to (a) identify potential classes (i.e., subgroups) of psychological flexibility based on responses on measures of key subcomponent process and (b) examine whether such classes could reliably differentiate levels of self-reported psychological distress and positive and negative emotionality. We found three distinct classes: (a) High Psychological Flexibility, (b) Moderate Psychological Flexibility, and (c) Low Psychological Flexibility. Those in the Low Psychology Flexibility class reported highest levels of psychological distress, whereas those in the High Psychological Flexibility class reported lowest levels of psychological distress. This study provides a clearer view to clinicians of the profile of the broader spectrum of the psychological flexibility model to facilitate change in clients.